PEMBUATAN PUPUK BOKASHI DARI SAMPAH LINGKUNGAN BERDASARKAN RANCANGAN PERCOBAAN CAMPURAN YANG OPTIMUM PADA MODEL PERMUKAAN MULTIRESPON - Ruslan; Susanti Linuwih; Purhadi; Sony Sunaryo; Sri Nurhatika (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2009)
Environment waste arround ITS college such as waste of Trembesi leaves, Sono leaves, and Satintail at this research will be used as part of materials of Bokashi fertilizer producing. The first aim of this research produced Bokashi fertilizer in various proportion waste of Trembesi leaves, Sono leaves, and Satintail with other materials proportion which has been assumed to be constant based on development of optimum mixture design of multiresponse surface theory by D-optimum criterion. The second aim of this research was compared 5:3:1:1 composition from reference to 5:2:1:2 composition from researcher hypothesis with proportion of waste of Trembesi leaves, Sono leaves, and Satintail as independent variables to N, P, and K percentation as response variables. Optimum mixture designs of multiresponse surface model will be optimum if it weighted w = 1 / qs means the each point of experiment will be given s-replications as much as proportion number of experiment point to number of component. The 5:2:1:2 and 5:3:1:1 compositions of Bokashi fertilizer producing are not statistically difference, therefore both compositions can be used to produce Bokashi fertilizer.